2019
DOI: 10.1155/2019/5759694
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Infant Interaction during the First Year of Life in Infants at High Risk for Cerebral Palsy: A Systematic Review of the Literature

Abstract: Introduction. Perinatal adverse events put neonates at high risk for short and long-term disabilities, including cerebral palsy (CP). The most recent guidelines about early intervention in infants with brain damage have emphasized the importance of family involvement from the very first phases of development. Early parent-infant interactions are pivotal in promoting infant cognitive and social developmental trajectories. However, little is known about the extent to which severe adverse perinatal events can aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 63 publications
2
20
0
3
Order By: Relevance
“…One reviewed the extent to which families were involved in early intervention but did not evaluate the effectiveness of the interventions themselves, 24 one reviewed coaching practices but did not consider child outcomes, 25 and one focused solely on parentchild interactions, not development. 26 One was on older children, 27 two included mixed or other diagnoses, 28,29 and three did not involve younger children and/or were not about CP exclusively. [30][31][32] Table 1 summarizes the data from each of the systematic reviews, including details from each of the included studies and indicating overlap where present.…”
Section: Resultsmentioning
confidence: 99%
“…One reviewed the extent to which families were involved in early intervention but did not evaluate the effectiveness of the interventions themselves, 24 one reviewed coaching practices but did not consider child outcomes, 25 and one focused solely on parentchild interactions, not development. 26 One was on older children, 27 two included mixed or other diagnoses, 28,29 and three did not involve younger children and/or were not about CP exclusively. [30][31][32] Table 1 summarizes the data from each of the systematic reviews, including details from each of the included studies and indicating overlap where present.…”
Section: Resultsmentioning
confidence: 99%
“…Investigating the emotional, psychological and stressful consequences of the COVID-19 emergency for the primary caregivers of children with neurodevelopmental disabilities is key to promote timely and appropriate support for parents as well as for the children themselves. Indeed, several studies suggest that parental well-being is linked with the quality of parenting even in the presence of neurodevelopmental conditions [9,10]. Caregivers are well-recognized as the primary source of prevention and care for children [11] and they can provide relevant stimulation to promote long-term cognitive, language and socio-emotional development up to preschool-and school-age [6,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, parenting represents a key factor to promote the physical, socio-emotional, behavioral, and cognitive development of infants and children (Perrin et al, 2016;Provenzi et al, 2018). The role of parenting is much more relevant when infants and children present special healthcare needs due to neurodevelopmental risk or disabilities (Festante et al, 2019). Recent research shows that maximizing parental engagement and targeting parents' caregiving skills alongside infants' needs and disabilities are crucial for the success of early rehabilitation programs (Britto et al, 2017;Schuster and Fuentes-Afflick, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these interactive and relational difficulties can ultimately increase the risk of developing behavioral problems in children (Spittle and Treyvaud, 2016). Importantly, several studies have documented that the quality of parenting is associated with children's developmental outcomes, even in the presence of ND (Spiker et al, 2002;Assel et al, 2003;Festante et al, 2019). It has been shown that, beside social interaction and emotional support, parents also provide cognitive stimulation during their exchanges with their children, with long-term benefits for cognitive, language, and socio-emotional outcomes up to preschool-and school-age (Anderson et al, 2013;Innocenti et al, 2013;Totsika et al, 2019).…”
Section: Introductionmentioning
confidence: 99%